ANALISA ELECTRODE CONSUMABLE TYPE OK AUTROD 12.10 DENGAN PENGELASAN SUBMERGED ARC WELDING (SAW) PADA BLOCK KAPAL DCV 18500 DWT DI PT. JASA MARINA INDAH SEMARANG - Kiryanto, Kiryanto; Sasmito Hadi, Eko (Diponegoro University, 2010)
In this of globalization is growing very rapidly advancing technology. As well as in shipyard industry is toshipbuilding process. Submerged Arch Welding (SAW) is as joint methode of ship construction. Purpose ofresearch know number of electrodes wich requirement on block welding the ship DCV 18500 DWT in JasaMarina Indah Shipyard Semarang.The specimen experiment used is ST 42 low carbon steel. Variation of plates tickness is 12, 13, 14, 17, 19 and24 mm. Research step is carried out by making the specimen with variation thickness respectively. Specimendimensions length x width is 500 mm x 50 mm. The number of each specimen was made of three pieces. Thendo the measurement welding length, length and weight electrodes and slag welding.The analysis result of data welding on the specimen can be known number of electrode s and fluxs inSubmerged Arch Welding (SAW). The aplication of this research is the block DB 5(p/c/s), SS5A(p/s), SS5B(p/s), UD 5C, and TB 102 (p/c/s. Weight of consumable electrodes is 2185.31 kg (73 roll) and number offlux used wight is 2967.95 kg (119 bag).